Celia M. Deutsch, Eugene J. Fisher, and James Rudin, Eds. Toward the Future: Essays on Catholic-Jewish Relations in Memory of Rabbi León Klenicki - Svartvik, Jesper (Studies in Christian-Jewish Relations, 2014)
No abstract is available.